A keeper of many crypts: a behaviour-manipulating parasite attacks a taxonomically diverse array of oak gall wasp species. (27th September 2019) - Ward, Anna K. G.; Khodor, Omar S.; Egan, Scott P.; Weinersmith, Kelly L.; Forbes, Andrew A.
Abstract : Parasites of animals and plants can encounter trade-offs between their specificity to any single host and their fitness on alternative hosts. For parasites that manipulate their host's behaviour, the added complexity of that manipulation may further limit the parasite's host range. However, this is rarely tested. The recently described crypt-keeper wasp, Euderus set, changes the behaviour of the gall wasp Bassettia pallida such that B. pallida chews a significantly smaller exit hole in the side of its larval chamber and 'plugs' that hole with its head before dying. Euderus set benefits from this head plug, as it facilitates the escape of the parasitoid from the crypt after it completes development. Here, we find direct and indirect evidence that E. set attacks and manipulates the behaviour of at least six additional gall wasp species, and that these hosts are taxonomically diverse. Interestingly, each of E. set 's hosts has converged upon similarities in their extended phenotypes: the galls they induce on oaks share characters that may make them vulnerable to attack by E. set . The specialization required to behaviourally manipulate hosts may be less important in determining the range of hosts in this parasitoid system than other dimensions of the host–parasitoid interaction, like the host's physical defences.